2017
DOI: 10.18632/oncotarget.15994
|View full text |Cite
|
Sign up to set email alerts
|

α2,3-sialyltransferase type I regulates migration and peritoneal dissemination of ovarian cancer cells

Abstract: Epithelial ovarian cancer (EOC) has the highest mortality rate among gynecologic cancers due to advanced stage presentation, peritoneal dissemination, and refractory ascites at diagnosis. We investigated the role of α2,3-sialyltransferase type I (ST3GalI) by analyzing human ovarian cancer datasets and human EOC tissue arrays. We found that high expression of ST3GalI was associated with advanced stage EOC. Transwell migration and cell invasion assays showed that high ST3GalI expression enhanced migration of EOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 57 publications
(55 reference statements)
1
24
0
Order By: Relevance
“…It has been suggested that the increased expression of ST3GAL1 in ovarian serous carcinoma may contribute directly to increased alpha2,3-linked sialylation 36 . Recent research supports our finding that ST3GAL1 expression is increased in serous ovarian cancer and demonstrates that ST3GAL1 may regulate ovarian cancer cell migration and peritoneal dissemination via epidermal growth factor receptor (EGFR) signaling 37 . The EGFR signaling pathway is known to be overexpressed and associated with poor prognosis in more than 70% of ovarian cancer patients 38 .…”
Section: Discussionsupporting
confidence: 79%
“…It has been suggested that the increased expression of ST3GAL1 in ovarian serous carcinoma may contribute directly to increased alpha2,3-linked sialylation 36 . Recent research supports our finding that ST3GAL1 expression is increased in serous ovarian cancer and demonstrates that ST3GAL1 may regulate ovarian cancer cell migration and peritoneal dissemination via epidermal growth factor receptor (EGFR) signaling 37 . The EGFR signaling pathway is known to be overexpressed and associated with poor prognosis in more than 70% of ovarian cancer patients 38 .…”
Section: Discussionsupporting
confidence: 79%
“…In prostate cancer, overexpression of galectin-4 relates to malignancy because it binds on the O -linked carbohydrate antigen T ( Table 1 ), activating EGFR/ERBB2 signaling [ 124 ]. On the other hand, a positive relationship among the expression of ST3GAL1, the enzyme thatconverts the T antigen in sialyl-T antigen ( Table 1 ), EGFR signaling and malignancy has also been documented [ 71 ].…”
Section: How Glycosylation Modulates the Activity Of Specific Recementioning
confidence: 99%
“…The results showed that both MAL-SG (α2,3-sialylated glycan) and SNA-SG (α2,6-sialylated glycan) expression were higher in CCA compared to NBD and HP/DP, suggesting the possible association between the increase of sialylation and CCA development. Although the mechanisms underlying the increase of sialylation in CCA were not yet clearly defined, it is possible to be triggered by the increase of sialic acid synthesis or sialyltransferases and/or the decrease of sialidases, as was shown previously in other cancers [33,36,37].…”
Section: Discussionmentioning
confidence: 74%
“…An association between the increased sialylation and cancer progression has been demonstrated in various cancers as it plays important roles in metastasis, immune evasion, radioresistance, and chemoresistance [21,[37][38][39]. Elevation of α2,3-sialylated-glycans via increase of α2,3-sialyltransferase was associated with metastasis of gastric cancer [33] and the advanced stage of ovarian cancer [31].…”
Section: Discussionmentioning
confidence: 96%